Science journalism for development in the Global South: A systematic literature review of issues and challenges. (November 2019) - Nguyen, An; Tran, Minh
Based primarily on a systematic review of the relevant literature between 2000 and 2017, this article reflects on the state of journalism about science in developing countries, with a focus on its issues, challenges and implications for their developmental processes and causes. Five major themes emerge from our analysis: (a) heavy dependence on foreign sources, especially the media of the Global North; (b) the low status of domestic science news in newsrooms; (c) uncritical science reporting that easily lends itself to influences of non-science vested interests; (d) tight grip of politics on science journalism; and (e) ineffective relationships between science and journalism. We will demonstrate that, while some of these problems exist in the North, they can have far more severe consequences on the progress of the South, where news plays an almost exclusive role in informing and engaging laypeople with science and its socio-cultural, economic and political implications.